2015
DOI: 10.1038/ijir.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in interactions between nucleus accumbens and visual cortex by explicit visual erotic stimuli: an fMRI study

Abstract: Men tend to have greater positive responses than women to explicit visual erotic stimuli (EVES). However, it remains unclear, which brain network makes men more sensitive to EVES and which factors contribute to the brain network activity. In this study, we aimed to assess the effect of sex difference on brain connectivity patterns by EVES. We also investigated the association of testosterone with brain connection that showed the effects of sex difference. During functional magnetic resonance imaging scans, 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…The decreased brain activity can reduce the reuptake of dopamine back into the presynaptic neuron ( Santtila et al, 2010 ), thus lead to sustainable synaptic dopamine activation, and may eventually result in PE. Notably, the SFCD changed in nucleus accumbens and fusiform gyrus may interrupt the dopamine releasing ( Sanna et al, 2017 ), dopamine signal receiving ( Lee et al, 2015 ) and dopamine related neural activity ( Lee et al, 2015 ). The SFCD and ROI analysis results may imply the damaged cortex in the dopamine system might be the pathological basis underlying PE.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased brain activity can reduce the reuptake of dopamine back into the presynaptic neuron ( Santtila et al, 2010 ), thus lead to sustainable synaptic dopamine activation, and may eventually result in PE. Notably, the SFCD changed in nucleus accumbens and fusiform gyrus may interrupt the dopamine releasing ( Sanna et al, 2017 ), dopamine signal receiving ( Lee et al, 2015 ) and dopamine related neural activity ( Lee et al, 2015 ). The SFCD and ROI analysis results may imply the damaged cortex in the dopamine system might be the pathological basis underlying PE.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while VS activity does not necessarily indicate sexual arousal, it can nonetheless be used to assess relative degrees of motivation while viewing sexual stimuli 28 47 48 . That is, relatively greater VS activity in response to either male or female erotic images would be consistent with relative androphilic or gynephilic preferences, respectively.…”
Section: Neural Correlates Of Sexuality and Rewardmentioning
confidence: 99%
“…Various brain imaging studies have shown sex differences in the pattern of response to sexual stimuli (e.g., Sabatinelli et al, ), in several cases with neural responses correlating with subjective arousal (Karama et al, ; Costa et al, ). Lee et al () found that men and women had distinct patterns of functional connectivity when viewing sexually explicit visual stimuli, and, in men, the activity in a network connecting visual and frontal areas was correlated with plasma testosterone levels.…”
Section: Sex Differences In High‐level Visionmentioning
confidence: 99%